An Analytic Hierarchy Process approach using multiple raters for the selection of complex technologies. (October 2021) - Wood, James B; Mason, Jessica L; Bianchini, Alessandra
The Department of Defense utilizes complex technologies in numerous fields; each technology must comply with specific parameters and system capabilities. In this selection of a complex technology best meeting prescribed capabilities, the parameter set includes nine areas, which have sub-areas. To handle the complexity of the process, the team identified the Analytical Hierarchy Process (AHP), a methodology providing a reliable solution. The AHP produced an importance coefficient for each area and sub-area, which were combined in the final phase of the ranking process. Users and technical support personnel agreed that the selected system met the requirements, field operational needs, and maintenance requisites. The AHP approach represents a viable tool to handle group decisions in support of technology management and related selection processes.